Cardiovascular and perceptual stress of female basketball referees during women`s International matches - Vaquera, A.; Mielgo-Ayuso, J.; Calleja-Gonzalez, J.; Leicht A. S. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The current aims were to determine body composition (BC), and heart rate (HR) and rating of perceived effort (RPE) responses by female basketball referees during elite international competition.